Bioactive constituents of the stem bark of Bersama abyssinica Fresen subsp. abyssinica Verdc. (Melianthaceae) - Vanessa Charnele Tsafack; Appolinaire Kene Dongmo; Raymond Ngansop Nono; Georges Bellier Tabekoueng; Beate Neumann; Hans-Georg Stammler; Jean Jules Kezetas Bankeu; Siméon Fogué Kouam; Pépin Nkeng-Efouet-Alango; Bruno Ndjakou Lenta; Norbert Sewald; Jean Rodolphe Chouna (Phytochemistry Letters, 2024)

Foetidumins A-D, and other chemical constituents from Helichrysum foetidum (L.) Moench (Asteraceae) with antiparasite activity - Hermine Wete Nono; Arno Rusel Donfack Nanfack; Billy Toussie Tchegnitegni; Cyrille Armel Njanpa Ngansop; Faustine Léonie Mafodong Dongmo; Maurice Ducret Awouafack; Fabrice Fekam Boyom; Bruno Lenta Ndjakou; Hans-Georg Stammler; Beate Neumann; Norbert Sewald; Silvère Augustin Ngouela (Phytochemistry, 2023)

Der Eisenstoffwechsel und seine Bedeutung für das Höhentraining - Georg Neumann; Kuno Hottenrott; Laura Hottenrott (German Journal of Exercise and Sport Research, 2021)
Zusammenfassung Ein Eisenmangel und eine katabole Stoffwechsellage behindern die Zunahme des Gesamthämoglobins und damit einen Anstieg der Sauerstofftransportkapazität, sodass die Wirksamkeit des Höhentrainings herabgesetzt ist. Die Eisenhomöostase wird sehr fein durch das hepatische Hormon Hepcidin (HEPC) kontrolliert, welches die Eisenaufnahmefähigkeit der Darmzellen über ein spezielles Protein, dem Ferroportin, kontrolliert. Unter Hypoxie stimuliert das Protein HIF-1 α die Freisetzung des Erythropoitins (EPO). Unzureichende Eisenspeicher und/oder eine Vitamin-B12-Unterversorgung bei Athleten, besonders bei jungen Frauen, sind Wochen vor einem Höhentraining durch eine orale Eisen- und/oder Vitamin-B12-Substitution unter ärztlicher Kontrolle, aufzufüllen. Voraussetzung für eine leistungsfördernde Wirkung des Höhentrainings ist ein mehrmaliger Aufenthalt in mittleren Höhen von 1700 m bis 3000 m. Als Aufenthaltsdauer werden 350 h bis 500 h oder zwei bis drei Wochen empfohlen. Mangelnde Eisenverfügbarkeit und ein Energiedefizit können die Wirksamkeit des Höhentrainings negativ beeinflussen. Liegt aus medizinischer Sicht eine Eisenunterversorgung vor, dann wird zu einer oralen Supplementation vor und während des Höhentrainings geraten. Bei normaler Eisenverfügbarkeit führt die gesteigerte Hämatopoese durch EPO zur Zunahme des Gesamthämoglobins. Die Wirkung des hypoxieinduzierten Hämoglobinanstiegs ist nach dem Höhentraining auf drei bis vier Wochen begrenzt.

Detection of Colchicum autumnale in drone images, using a machine-learning approach - Lukas Petrich; Georg Lohrmann; Matthias Neumann; Fabio Martin; Andreas Frey; Albert Stoll; Volker Schmidt (Precision Agriculture, 2020)
Colchicum autumnale are toxic autumn-blooming flowering plants, which often grow on extensive meadows and pastures. Thus, they pose a threat to farm animals especially in hay and silage. Intensive grassland management or the use of herbicides could reduce these weeds but environment protection requirements often prohibit these measures. For this reason, a non-chemical site- or plant-specific weed control is sought, which aims only at a small area around the C. autumnale and with low impact on the surrounding flora and fauna. For this purpose, however, the exact locations of the plants must be known. In the present paper, a procedure to locate blooming C. autumnale in high-resolution drone images in the visible light range is presented. This approach relies on convolutional neural networks to detect the flower positions. The training data, which is based on hand-labeled images, is further enhanced through image augmentation. The quality of the detection was evaluated in particular for grassland sites which were not included in the training to get an estimate for how well the detector works on previously unseen sites. In this case, 88.6% of the flowers in the test dataset were detected, which makes it suitable, e.g., for applications where the training is performed by the manufacturer of an automatic treatment tool and where the practitioners apply it to their previously unseen grassland sites.

Crystal structure and configuration revision of 9-hydroxy-7,8-dehydro-sarcotrocheliol and sarcotrocheliol - Abdelaaty Hamed; Marwa Y. Issa; Mohamed A. Ghani; Marcel Frese; Beate Neumann; Hans Georg Stammler; Norbert Sewald; Mohamed Shaaban (Natural Product Research, 2019)

Aquifer community structure in dependence of lithostratigraphy in groundwater reservoirs - Andrea Beyer; Michael Rzanny; Aileen Weist; Silke Möller; Katja Burow; Falko Gutmann; Stefan Neumann; Julia Lindner; Steffen Müsse; Hanka Brangsch; Jennifer Stoiber-Lipp; Martin Lonschinski; et al. (Environmental Science and Pollution Research, 2015)

Methods from the Theory of Random Heterogeneous Media for Quantifying Myocardial Morphology in Normal and Dilated Hearts - Rudolf Karch; Friederike Neumann; Robert Ullrich; Georg Heinze; Josef Neumüller; Bruno K. Podesser; Martin Neumann (Annals of Biomedical Engineering, 2010)

The effect of Palamed G bone cement on early migration of tibial components in total knee arthroplasty - H. Kienapfel; R. Hildebrand; T. Neumann; R. Specht; M. Koller; I. Celik; H.H. Mueller; P. Griss; K.J. Klose; C. Georg (Inflammation Research, 2004)